Zero charisma [videorecording (DVD)] - Matthews, Andrew (Andrew J.); Eidson, Sam; England, Brock; Graham, Garrett (Cinedigm, 2014)
As the strict Game Master of a fantasy role-playing game, Scott leads his friends in a weekly quest through mysterious lands from the safety of his grandmother's kitchen. But his mastery of his own domain starts to slip, along with everything else.